Insights Into Histoplasma capsulatum Behavior on Zinc Deprivation - Assunção, Leandro do Prado; Moraes, Dayane; Soares, Lucas Weba; Silva-Bailão, Mirelle Garcia; de Siqueira, Janaina Gomes; Baeza, Lilian Cristiane; Báo, Sônia Nair; Soares, Célia Maria de Almeida; Bailão, Alexandre Melo (Frontiers in Cellular and Infection Microbiology, 2020)
Histoplasma capsulatum is a thermodimorphic fungus that causes histoplasmosis, a mycosis of global incidence. The disease is prevalent in temperate and tropical regions such as North America, South America, Europe, and Asia. It is known that during infection macrophages restrict Zn availability to H. capsulatum as a microbicidal mechanism. In this way the present work aimed to study the response of H. capsulatum to zinc deprivation. In silico analyses showed that H. capsulatum has eight genes related to zinc homeostasis ranging from transcription factors to CDF and ZIP family transporters. The transcriptional levels of ZAP1, ZRT1, and ZRT2 were induced under zinc-limiting conditions. The decrease in Zn availability increases fungicidal macrophage activity. Proteomics analysis during zinc deprivation at 24 and 48 h showed 265 proteins differentially expressed at 24 h and 68 at 48 h. Proteins related to energy production pathways, oxidative stress, and cell wall remodeling were regulated. The data also suggested that low metal availability increases the chitin and glycan content in fungal cell wall that results in smoother cell surface. Metal restriction also induces oxidative stress triggered, at least in part, by reduction in pyridoxin synthesis.